Meningkatkan Keterampilan Sosial Siswa Melalui Penerapan Pembelajaran Kooperatif Tipe Teams Games Tournament - Rahmah, Siti; jamal, M. Arifuddin; Suyidno, Suyidno (Berkala Ilmiah Pendidikan Fisika, 2014)
Teaching and learning Process by teacher center on class effect at the skill of student social. Low of studentsâ skill during teaching and learning process of Physics study indirectly low influencing of studentsâ learning result. Therefore the researcher did the research with the aim to uplift skill class student social of XI TGB B SMNKN 5 Banjarmasin at static fluid discussion fundamental through applying of the study of type co-operative of Team games of Tournament. This Research type of Class Action Research (CAR) model Hopkins Which the research consist of 3 cycles, every cycle cover planning, observation and perception, and also reflection. The subject of the research is 20 class student of XI. This Matter is caused by done/conducted] study still centrally [at] teacher without entangling student actively. [Is] therefore done by research with the aim to increase the skill of student social by applying the model study of type co-operative of TGT. Data obtained to through etiquette, observation, test, and documentation. Data analyze descriptively qualitative and quantitative. Result of data analysis shows 1) the result of lesson plan [at] cycle of I, II, and III each of 63 %, 64 %, and 73 2) uplifting of skill of social [at] cycle of I, II, and III each of 27 %, 44 %, and 43,7 3) result learn student [at] cycle of I, II, and III eachÂ  0 %, 50 %, and 5,29 %, and 4) student response to model study of type of TGT unfavourable in general. Â